Posttraumatic Growth and Coping Strategies Among Patients With Head and Neck Cancer: Do Approach Coping and Avoidant Coping Predict Posttraumatic Growth Over Time? - Nik Jaafar, Nik Ruzyanei; Abd Hamid, Norhaliza; Hamdan, Nur Amirah; Rajandram, Rama Krsna; Mahadevan, Raynuha; Mohamad Yunus, Mohd Razif; Zakaria, Hazli; Leong Bin Abdullah, Mohammad Farris Iman (Frontiers in Psychology, 2021)
Despite an enormous number of studies addressing the importance of posttraumatic growth (PTG) among cancer patients, the literature lacks data regarding how different coping strategies affect PTG among head and neck cancer (HNC) patients over time. This longitudinal study investigated the PTG trend and coping over five to seven months among a cohort of HNC patients within the first year after their diagnosis. It determined an association between coping strategies and PTG over time. The study’s HNC respondents were administered a socio-demographic and clinical characteristics questionnaire during their baseline assessments. Additionally, the Malay versions of the “Posttraumatic Growth Inventory-Short Form” (PTGI-SF) and the “Brief Coping Orientation to Problems Experienced Inventory” (Brief COPE) were administered during respondents’ baseline assessments and follow-up assessments (five to seven months after the baseline assessments). In total, 200 respondents reported an increasing PTG trend and approach coping (active coping, planning, positive reframing, acceptance, emotional support, and instrumental support) and a decreasing trend of avoidant coping (self-distraction and denial) over time. Two approach coping strategies (acceptance and planning) significantly increased PTG while denial was the only avoidant coping strategy that significantly lowered PTG, after controlling for socio-demographic and clinical characteristics, over time. Our study’s findings identified the need to incorporate psychosocial interventions that enhance approach coping and reduce avoidant coping into HNC patients’ treatment regimes.